Old Babylonian Grammar : Volume One - Streck, Michael P., (Handbook of Oriental Studies. Section 1 The Near and Middle East ;, 2022)
The book contains a descriptive grammar of Old Babylonian, the best attested period and dialect of Akkadian. Volume 1 describes the orthography, phonology, nouns, pronouns and numbers of Old Babylonian.